La comunicación oral en inglés en estudiantes del sexto ciclo de educación básica regular turno mañana y tarde en la institución educativa pública Maynas, Iquitos 2020 - Guerrero Vargas, Jeniffer Ximena (2022)
The purpose of this study was to compare sixth cycle students’ achievement of oral communication in English at Maynas secondary school, Iquitos 2020, according to school shifts. The research was of a comparative type with field study, transectional contemporary, and univariable designs. The population was made up by 421 students with a deterministic sample of 183: 102 students of the morning shift and 81 students of the afternoon shift. Data gathering tools used were valid and reliable oral comprehension test, speaking performance test, and rubric. Results show that both shifts are at the same level achievement of oral communication, as their mean scores were 7,104 and 7,224. In its dimensions: Getting information (15,677>15,218) “expected achievement”, inferencing and interpreting information (17,300>17,170) “expected achievement”, use of non-verbal and paraverbal resources (13,257<13,433) “in process”, and strategic interaction (2,685<2,730) “Pre-beginner”. In conclusion, the Mann-Whitney U test for independent samples showed that there is no statistically significant difference between the two groups of the study population as p-value = 0.319 ? ? = 0,05 rejecting the working hypothesis.